L’habit et l’ordre social : le témoignage de l’Histoire Auguste - Callu, Jean-Pierre (Antiquité Tardive - Late Antiquity - Spätantike - Tarda Antichità, 2005)
Abstract Three passages in the Historia Augusta will be examined: 1°) Alex. Sev. 42, 1. The uestis balnearis mitigates the egalitarian nakedness of the baths ; 2°) Tac. 16, 1-2. Five representations of the Emperor are compared; among others, the image of the uenator which draws attention towards the segmenta of tunics, that of the clamydatus towards the military uniform and its possible grades; 3°) Alex. Sev. 27, 1. The project of a distinctive dress for civilian officials met with the theodosian constitution of 382 which instituted the wearing of a contrastingly coloured tablion for an increasing bureaucracy.